Productivity of Sumateran Composite dan Barbados Cross sheep breed in the field condition - Setiadi, Bambang; ., Subandriyo (Indonesian Journal of Animal and Veterinary Sciences, 2007)
Two years field study has been carried out in the Purwakarta district , West Java, to evaluate sheep productivity of Sumateran Composite (K) and Barbados cross (BC) breeds introduced to the farmers, compared with locally thin tail sheep breed (L) that were maintained by the farmers. Genotype compositions of K sheep were Barbados Blackbelly 25%, St. Croix 25%, and Sumateran sheep 50%; and for BC were Barbados Blackbelly 50% and Sumateran sheep 50%. Sheep those were introduced was new breed from breeding improvement of Indonesian Research Institute for Animal Production. Litter size of K, BC, and L ewes was 1.3; 1.4; and 1.5 respectively. Pre-weaning mortality rate were 5.0; 5.0 and 8.0% respectively for K, BC, and L lambs. Ewe Reproduction Rate (LRI = number of lamb at weaning/ewe/year) of L (2.14) was higher than BC (2.0) and K (1.85). The ewe productivity (PI = kg lambs/ewe/year) is the average of weaning weight timed LRI. Because the weaning weight of L (7.0 kg) were significantly lowest than BC (10.5 kg) and K (9.25 kg) will affect on PI. PI of L (14.98) ewe were significantly (P<00.5) lowest than BC (21) and K (17.11). Body weight of crossbred (K X L and BCxL) under the same physiologic status were similarly with BC and K. According to the result of productivity evaluation of introduced sheep breed in the field condition, can be sumarize that productivity of K and BC sheep were significantly better than locally thin tail sheep. Key Words: Sumatera Composite, Barbados Blackbelly, Thin Tail Sheep, Productivity, Traditional Rearing